Sharing Session Strategi Peningkatan Produktivitas di kalangan Pelaku UMKM - Sufiati Sufiati; Sitti Mispa; Zulkifli Soekarno; Nurlaeli Razak; Andi Dahrul; Dharmawati Djaharuddin; Yudi Akhmad Sadeli (CV. Aksara Global Akademia, 2024)
This sharing session activity aims to find solutions to the problem of increasing business productivity among MSME players. This activity is the result of a collaboration between STIEM Bongaya Makassar and the Bali chapter of the TDA foundation which was held at the Wistara cafe, Badung Regency, Bali with the theme of MSME revival activities. The activity method is carried out through sharing sessions by forming a group discussion forum (FGD) where the presenters and participants provide input to each other and formulate appropriate strategies to increase business productivity. One of the conclusions obtained is that increasing productivity among Micro, Small and Medium Enterprises (MSMEs) can be the key to business success and growth in the form of increasing production efficiency, improving product quality, improving marketing, improving skills and knowledge, increasing cooperation.